The Ring Ladies of Semban - Hishamuddin, Siri (Unit Penerbitan UiTM Perak, 2025, 2025)
FASA 6.0: Malaysia Negaraku is a visual anthology that captures the spirit and complexity of Malaysian identity through the art of photography. Developed by the Department of Photography and Creative Imaging, UiTM Perak, in collaboration with Humanika Artspace in Bandung, Indonesia, the book features 27 photographic works by Malaysian artists, ranging from students to professionals. These images explore themes such as cultural heritage, community, tradition, and national symbolism. Artist statements and critical reflections offer deeper insight into each piece, connecting personal narratives with national discourse. Set against the backdrop of cross-cultural dialogue in Bandung, the project affirms photography as a medium of storytelling, preservation, and transformation. This book invites readers to reflect on the role of visual art in shaping collective memory and imagining Malaysia’s future.